Pengaruh Integrasi Tanaman dan Ternak Sapi terhadap Peningkatan Pendapatan dan Produktivitas Petani (Studi Kasus : Petani Kentang di Kecamatan Harian, Kabupaten Samosir) - Lyndon Parulian; Kiki Pagar S.M. Munthe; Ruth Dameria Haloho (Fakultas Pertanian, Universitas Timor, 2019)
This study aims to determine the effect of integrated farming systems of plants and cattle on plant productivity and increase in farmer’s income in the daily Subdistrict of Samosir Regency. This research was conducted in the Partungko Naginjang, Janji Martahan, and Siparmahan in Harian Subdistrict, Samosir Regency. The method of this research is a case study. The data analysis used is the t-Test. The conclusion of this study is that integrated farming of crops and cattle has a significant impact on increasing land productivity with potato crops per farmer participant integrated farming is higher than farmers not participants, with differences in land productivity of 0,99 tons per hectare and integrated crop farming and cattle have a significant impact on increasing farmer’s income. The average income of integrated farmer participant per planting season is higher than the income of farmers who are not the participant with the differences in income IDR 11,562,968 per Ha. The farmers who have not utilized the integration of plants and cattle are expected to participate as participants because this program provide an increase and productivity.